Epidemiological characteristics of pertussis in Estonia, Lithuania, Romania, the Czech Republic, Poland and Turkey 1945 to 2005 - (:unkn) unknown (SPRINGER, 2009)
Pertussis epidemiology was examined in selected Central and Eastern European countries andTurkey (CEEs) from 1945 to 2005. Epidemiology and immunisation coverage data were collected fromNational Health Departments and Epidemiology Institutes. Pertussis diagnosis was made by the World Health Organization (WHO) clinical criteria, laboratory confirmation and/or epidemiological link, except for Romania (WHO clinical case definition used). In the pre-vaccine era, pertussis incidence (except Turkey) exceeded 200/100,000 (range180-651/100,000), with 60-70% of cases occurring in pre-school children. Until 2007, a second-year booster was givenin Estonia, Lithuania and Turkey, and an additional pre-school booster elsewhere. During 1995-2005, immunisation coverage by the age of 2 years exceeded 80% (range 80-98%) and, excluding Estonia, pertussis incidence was < 3/100,000. Age-specific incidence rates rose in 5-14 year olds in Poland, Estonia and the Czech Republic. Incidence rates in children < 1 year of age remained unchanged. There were two age distribution patterns. In the Czech Republic and Estonia, 16% of cases occurred in pre-school children and 17% and 22% in children > 15 years of age, respectively; in Romania, Turkey and Lithuania, 51%, 71% and 73%, respectively, occurred in pre-school children and < 7% in children aged > 15 years.Pertussis infection persists, despite high immunisation coverage. Compared with the pre-vaccine era, the age distribution changed differentially in CEEs, with an apparent shift towards older children.
Keywords: Pertussis; Epidemiology; Europe; Vaccination; BORDETELLA-PERTUSSIS; CHILDREN; INFECTIONS